Ein Extremalindikator für die ganzen Funktionen mit positiven Nullstellen - Kondratjuk, A. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. А. Кондратюк. Экстремальный индикатор для целых функций с положительными нулями A. Kondratiuk. Sveikos funkcijos su teigiamais nuliais ekstremalinis indikatorius